Common microorganisms causing onychomycosis in tropical climate - Leelavathi .M,; Tzar .M.N,; Adawiah .J, (Universiti Kebangsaan Malaysia, 2012)
Onychomycosis is the infection of nail apparatus by dermatophytes, yeasts or non-dermatophyte moulds and is responsible for 50% of all nail disorders. A five year retrospective study was conducted at Universiti Kebangsaan Malaysia to identify the common pathogens responsible for onychomycosis and to describe the epidemiology of the affected patients. A total of 278 abnormal nails were cultured, out of which 231 were positive for fungus. Females constituted 50.2% (n=116) while males 49.8% (n=115). The majority (51.9%, n=120) were between ages 50-69 years. The Malay ethnic group was most commonly affected (44.2%, n=102) followed by Chinese (33.8%, n=78), Indians (18.2%, n=42) and other ethnic groups (3.8%, n=9). The most common fungal element isolated was non-dermatophyte moulds (45.4%, n=105) followed by yeast (34.6%, n=80) and dermatophytes (1.3%, n=3). Aspergillus spp. was the commonest (59.8%,n=81) non-dermatophyte mould, while Candida spp. was the commonest yeast (74.3%, n=89) isolated. In this study, non-dermatophyte moulds are the most common microorganisms implicated to cause onychomysosis. Treatment for non-dermatophyte mould is challenging as the current available antifungal agents are more effective against dermatophytes and yeasts.